(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Introduction. The concept of a low-carbon economy is designed to solve the problem of climate change by transforming the socio-ecological-economic system based on the principles of zero greenhouse gas emissions. However, this issue is also addressed in most other environmentally oriented social concepts. The purpose of the article. The purpose of this article is to determine the place of the low-carbon economy within the system of modern environmentally oriented concepts of social development. Methods. The research was conducted by using general scientific and general economic methods. In particular, the most common methods were abstraction, generalization, comparison, induction, deduction, monographic method, axiomatic method, methods of retrospective and systematic analysis. Results. To achieve this goal, the author analyzed the most popular of environmentally oriented social concepts: the concept of sustainable development, the green economy concept, the blue economy concept, the concept of the blue (ocean) economy, and the circular economy concept. Additionally, a schematic model was constructed to illustrate the position of the low-carbon economy within the system of environmentally oriented concepts of social development. The study provides a retrospective analysis of the inception and evolutionary development of each of the researched concepts. Their guiding ideas, main principles, goals, and tasks were identified. Furthermore, the article differentiates between complementary and interchangeable concepts and shows the horizontal and vertical connections among the reviewed concepts. It was established that the issue of global warming is considered in each of the analyzed concepts. Moreover, the relationship between the analyzed concepts and the low-carbon economy concept was examined. Conclusions. Based on the results of the research, it can be concluded that the low-carbon economy concept consolidates measures and mechanisms to address the important and urgent problem of climate change. Within the system of environmentally-oriented social concepts, the investigated concept occupies the place of a specialized concept focused on reducing greenhouse gas emissions and combating climate change to achieve green growth and sustainable development. It is closely related to several other concepts through the common goal of finding ways to combat climate change. Consequently, the ideas of a low-carbon economy have become widespread in the concepts of sustainable development, the green economy, the blue economy, the blue (ocean) economy, and the circular economy.